Balinese Cultural Continuity: Heroine’s Role in Luh Ayu Manik Mas at War with the Spirit World - Yanuaresti Kusuma Wardhani; Yudhanita Pertiwi; Estrella T. Arroyo; Nurhadianty Rahayu; Zahratul Umniyyah (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This research explores the role of the heroine in preserving Balinese cultural identity, focusing on the character of Luh Ayu Manik Mas from the children's story,